THE PROTEIN AND WATER CONTENT OF TEN VARIATIONS OF THE FEED CASSAPRO OF YEAST TAPE - Indrawaty Sitepu (UPT Penerbitan Universitas Jember, 2016)
This research was conducted to find out how the protein and water content ten variations of the feed cassapro of yeast tape. This research was conducted in March-May 2016. The results showed manufacture of tapioca pulp and fish flour has increased very high protein after fermentation with yeast tape. Ten variations of feed cassapro of yeast tape according to the highest order as follows: variations 10, protein content of 66.12%; variation 9, protein content of 59.16%; variation 8, protein content of 67.54%; variation 7, protein content of 36.78%; variations 6, protein content of 38.14%; variation 5, protein content of 33.37%; variation 4, protein content of 26.82% variation 3, protein content of 24.76%; variation 2, protein content of 17.81%; the first variation, protein content of 68.63%. From the sequence can generally be seen that the higher the protein content if mixed fish flour higher. Although there are exceptions, namely the treatment of mixtures or variations first, seventh and ninth. It can be concluded that: the highest protein content of 66.12% was found in 10% variation cassapro blended with 90% fish flour and protein content of 17.81% is lowest that is a variation of 90% and 10% cassapro and fish flour. While most high water content is 17, 23% are on a variation of 80% and 20% tapioca pulp fish flour and the lowest water content is 6, 33% are on a variation of 10% tapioca pulp and 90% fish flour.